Can quantitative hepatitis B surface antigen levels predict the severity of liver disease in genotype E Patients?. Issue 1 (23rd August 2017) - Chakrabarty, Gayatri; Bruce, Matthew; Horner, Mary; Wang, Bo; Agarwal, Kosh; Carey, Ivana
Summary: The utility of quantitative Hepatitis B surface antigen (qHBsAg) level as a marker of chronic hepatitis B (CHB)‐related liver damage is not fully delineated, but is becoming increasingly relevant. Quantitative HBsAg levels are linked with progression of liver disease in HBeAg‐negative genotype B and C patients, but it is not clear whether this is consistent across all HBV genotypes. In this single‐centre, cross‐sectional observational study, we evaluated whether qHBsAg levels can predict the severity of liver disease in genotype E patients. Demographic characteristics, viral, biochemical markers and qHBsAg levels were assessed at time of liver biopsy [all HBV DNA>2000 IU/mL and/or abnormal alanine transaminase (ALT)]. Patients were divided into three groups according to the severity of fibrosis on biopsy: mild (F0‐1), moderate (F2‐4), severe (F5‐6) liver disease and into two groups according to the NI grading, low (NI 0‐3) and high inflammation (NI ≥4). A total of 259 HBeAg‐negative CHB treatment‐naive genotype E patients were studied. The median age of this cohort was 38 years, and 61% were males. Advanced (severe) fibrosis patients had higher ALT, HBV DNA, and lower HBsAg level and qHBsAg/DNA ratio. Patients with NI ≥4 had higher ALT, HBV DNA, but lower qHBsAg/DNA ratio. There was no correlation between HBsAg and HBV DNA levels. Quantitative HBsAg levels were lower in more advanced liver fibrosis. There was no correlation between qHBsAg and HBV DNA levels. This may reflect discordance between viral replication and transcriptional activity or differential HBsAg expression in HBeAg‐negative genotype E patients with advanced liver disease.